Rehabilitation of oropharyngeal dysphagia in children with cerebral palsy: A systematic review of the speech therapy approach - Hirata, Gisela Carmona; Santos, Rosane Sampaio (International Archives of Otorhinolaryngology, 2012)
Introduction: There are an estimated 30,000–40,000 new cases of cerebral palsy per year in Brazil. Motor disorders caused by cerebral palsy can lead to dysphagia as they may alter the preparatory, oral, pharyngeal, and esophageal phases.Aim: To identify existing rehabilitation methods of swallowing disorders in cerebral palsy, with emphasis on the pursuit of research using the Bobath concept, the Castillo Morales concept, oral sensorimotor therapy, and continuing education.Summary of the findings: We performed a systematic review of the medical and speech therapy literature on the rehabilitation of oropharyngeal dysphagia in children with cerebral palsy spanning 1977–2010 and from all languages and nations. Among the 310 articles retrieved, only 22 (7.09%) addressed therapeutic rehabilitation of oropharyngeal dysphagia in children with cerebral palsy. Of the 22 reports, 12 (54.5%) were from Canada, 3 (13.6%) were from Japan, 2 (9%) were from Brazil, 2 (9%) were from Germany, 1 (4.5%) was from the USA, 1 (4.5%) was from the United Kingdom, and 1 (4.5%) was from Poland. Of these reports, 63.6% used oral sensorimotor therapy as a therapeutic method, 36.3% reported continuing education as a therapeutic approach, and only 18.1% and 9% used the Bobath concept and Castillo Morales concept, respectively.Conclusion: Even with a constantly increasing cerebral palsy population, few studies include (re)habilitation in the treatment of oropharyngeal dysphagia in these children.
Keywords: cerebral palsy; deglutition disorders; rehabilitation